1997
DOI: 10.1021/ma970463y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Melting and Crystallization of Poly(ethylene oxide) in Real-Time by Hot-Stage Atomic Force Microscopy

Abstract: Crystallization and melting in poly(ethylene oxide) are followed in real-time using hotstage atomic force microscopy (AFM). Hedritic morphology is observed at various stages of development. Lamellar growth rates are estimated and found to agree with values obtained by conventional optical microscopy. The presence of a depletion zone is detected at the crystal/melt interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 26 publications
9
68
0
Order By: Relevance
“…The bright lines in the images (Fig. 2C) are consistent with those of a typical morphology common in lamellar structures (38); for thick specimens of stacked lamellae, moiré fringes may also contribute to the contrast. Because DF imaging is very sensitive to changes in structural order (lamellar crystallinity and orientation), the intensity variation in the images taken at different times is a complementary indication of the structural change.…”
Section: Structural Dynamicssupporting
confidence: 80%
“…The bright lines in the images (Fig. 2C) are consistent with those of a typical morphology common in lamellar structures (38); for thick specimens of stacked lamellae, moiré fringes may also contribute to the contrast. Because DF imaging is very sensitive to changes in structural order (lamellar crystallinity and orientation), the intensity variation in the images taken at different times is a complementary indication of the structural change.…”
Section: Structural Dynamicssupporting
confidence: 80%
“…Several groups have studied the crystallization behaviors and structures of semicrystalline polymers confined to nanoscopic spaces 1–3, 10–33. Frank and coworkers1–3 reported the substantial reduction of the crystallization rate in ultrathin films of poly(di‐ n ‐hexylsilane).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the AFM studies related to the development of the morphology in polymer systems are performed at room temperature [6][7][8]. Recently, some appealing investigations have shown that using intermittentcontact mode AFM equipped with a hot-stage, it is possible to follow, e.g.…”
Section: Introductionmentioning
confidence: 99%